Influência farmacogenética da enzima SOD2 na resposta in vitro ao resveratrol de células mononucleares - Capeleto, Dianni de Menezes (2014)
Resveratrol (RES) is an anti-aging molecule that provides both anti-inflammatory and antioxidant properties. However, it is unclear whether the basal oxidative state of the cell has any influence on the effects of this compound. In humans, a single nucleotide polymorphism (SNP) is present in the enzyme manganese superoxide dismutase (SOD2), localized in codon 16 (rs4880), which can either be an alanine (A) or valine (V). This SNP causes an imbalance in the cellular levels of SOD2, where AA- and VV-genotypes result in higher or lower enzy-matic activity, respectively. Furthermore, the VV-genotype has been associated with high levels of inflammatory cytokines. Here, we examined the effects of a range of RES concentra-tions on the in vitro activation of human peripheral blood mononuclear cells (PBMCs) carry-ing different Ala16Val-SOD2 genotypes. Cell proliferation (at 24 and 72 h) was analyzed using an MTT assay and several oxidative biomarkers and cytokines (IL-1β, IL-6, TNF-α, IFT-γ and IL-10) were also quantified. In addition, the effects of RES on the expression of the SIRT 1 gene were evaluated by qRT-PCR. We show that after 24 h exposure to RES, A-genotype PBMCs displayed a decrease in cell proliferation, whilst VV-cells contrasted this; although after 72 h, cell proliferation was similar in homozygous cells when compared to con-trol groups. At 10 μM RES, there was a significant decrease in the production of inflammato-ry cytokines in A-allele cells; however, VV-cells generally displayed a subtle decrease in the-se, except for TNF-α, which was not affected. In all SOD2 genotypes cells exposed to RES resulted in an upregulation of SIRT 1 levels. Together, these results suggest that the effect of RES on human PBMC activation is not universal and is dependent on the Ala16Val-SOD2 SNP.